Message Heard: Insights for Doctoral Program Design From Community Partners - Sharon L. Dormire PhD, RN; Jodie Gary PhD, RN; Cynthia Weston DNP, RN, FNP-BC; Brian Holland PhD, RN (SAGE Publishing, 2019)
Developing a nursing doctoral program requires, among other considerations, thoughtful reflection on opportunities for graduates, and needs of the health-care community. To educate nurse clinicians, scientists, and leaders prepared to address complex health-care issues, colleges of nursing must engage with community stakeholders during program development. One college embraced this opportunity to dialogue through a series of semistructured focus groups and surveys to inform community partners of the developing doctoral program plan and to hear their related ideas and opinions. Themes arising from qualitative data analysis included driving forces, the value of education, and differing doctoral roles. The findings were far more enlightening than anticipated and ultimately guided the direction of program development. This study affirmed the power of meaningful dialogue with community partners to ensure a well-educated nursing workforce with the skills needed to advance nursing practice in the changing health-care environment.